(3TQM GdQSGdI GdehShjI GdbjGSjI aj GdefWbs - (3eMeOGdeUWai GdCQVheis; (3ehSi GdHgdhGfjs
(3ChdgG (B:s
(3fMeOc jG ef aVdJfG HGdefWb GdUMjM hCfWbJfG s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B94 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs